Prevalence and change of central obesity among US Asian adults: NHANES 2011-2014 - Xuefeng Liu; Yang Chen; Nicole L. Boucher; Amy E. Rothberg (BMC, 2017)
Abstract Background Central obesity is a major risk factor for cardiometabolic diseases. The prevalence of central obesity has not been reported fully among Asian adults in the United States (US). Methods Cross-sectional data of 1288 Asian adults aged 20 years or over was selected from the US National Health and Nutrition Examination Survey with a stratified multi-stage sampling design. The prevalence of central obesity was calculated with 95% confidence intervals (CIs) and Chi-square tests were conducted to test the significance of the prevalence differences across characteristic groups. Results The overall prevalence of central obesity among US Asian adults was 58.1% in 2011-2014. The prevalence of central obesity was higher in older adults (73.5%) than in young adults (45.4%) (p < 0.0001). Women had 13.4% higher prevalence than men (64.4% vs 51.0%, p < 0.0001). The prevalence increased over time (2011-2012 vs 2013-2014) in young adults (39.2% vs 51.5%), men (45.4% vs 56.6%), adults with college education or above (54.2% vs 61.7%) and non-poor adults (55.4% vs 62.4%). Compared with men, women had higher prevalence in each subgroup of age, education, poverty, and length of time (except for the subgroup of "born in the US") (all p < 0.05) and in the subgroup of "married or living with partner" for marital status (p < 0.0001). Conclusion Central obesity is prevalent in Asian adults, particularly in older adults and women. More efforts are needed to prevent and treat obesity in Asian adults as Asians are incurring the greatest increase in type 2 diabetes in parallel with the rising rate of central adiposity.